2011
DOI: 10.1002/nau.21191
|View full text |Cite
|
Sign up to set email alerts
|

Increased bladder activity is associated with elevated oxidative stress markers and proinflammatory cytokines in a rat model of atherosclerosis‐induced chronic bladder ischemia

Abstract: Oxidative stress and inflammation may be key factors in the development of bladder overactivity in atherosclerosis-induced chronic bladder ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
100
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 90 publications
(114 citation statements)
references
References 31 publications
8
100
0
1
Order By: Relevance
“…Applying the combination of a high-cholesterol diet with balloon injury to the iliac artery in rats confirmed many findings from the rabbit model (Nomiya et al 2012a(Nomiya et al , 2012b. In those studies, atherosclerosis was reported not only for the iliac arteries abut also for bladder microvessels.…”
Section: Effects Of Chronic Hypoperfusion Of the Bladdersupporting
confidence: 64%
“…Applying the combination of a high-cholesterol diet with balloon injury to the iliac artery in rats confirmed many findings from the rabbit model (Nomiya et al 2012a(Nomiya et al , 2012b. In those studies, atherosclerosis was reported not only for the iliac arteries abut also for bladder microvessels.…”
Section: Effects Of Chronic Hypoperfusion Of the Bladdersupporting
confidence: 64%
“…Thus, the increase of the locomotor activity in the pelvic venous congestion rats that was observed in our current study suggests that naftopidil may have both a capillary stabilizing action, and inhibit the extravascular leakage of stimulatory substances that act on the bladder. In the atherosclerosis-induced chronic bladder ischemia rat model, changes in the urinary frequency were shown to be associated with an increase of oxidative stress markers in the urine or bladder tissue (17,19). Furthermore, atherosclerosis-induced chronic ischemic bladder also decreased constitutive nitric oxide synthase (NOS) (20).…”
Section: Discussionmentioning
confidence: 99%
“…Yoshida et al reported myocardial infarction-prone Watanabe Heritable Hyperlipidemic rabbits, an animal model for human familial 8 hypercholesterolemia and atherosclerosis, showed detrusor overactivity with decreased detrusor contraction 8 . Another study using the rat model of atherosclerosis-induced chronic bladder ischemia showed that reduction in BBF was associated with detrusor overactivity and urinary frequency 9 , and that the levels of oxidative stress markers and proinflammatory cytokines were increased in rats with chronic bladder ischemia 10 . In a clinical study using …”
Section: Discussionmentioning
confidence: 99%